Role of Transient Receptor Potential Ankyrin 1 Ion Channel and Somatostatin sst4 Receptor in the Antinociceptive and Anti-inflammatory Effects of Sodium Polysulfide and Dimethyl Trisulfide - Bátai, István Z.; Horváth, Ádám; Pintér, Erika; Helyes, Zsuzsanna; Pozsgai, Gábor (Frontiers in Endocrinology, 2018)
Transient Receptor Potential Ankyrin 1 (TRPA1) non-selective ligand-gated cation channels are mostly expressed in primary sensory neurons. Polysulfides are Janus-faced substances interacting with numerous target proteins and associated to both protective and detrimental processes. Activation of TRPA1 in sensory neurons, consequent somatostatin (SOM) liberation and action on sst4 receptors have recently emerged as mediators of the antinociceptive effect of organic trisulfide dimethyl trisulfide (DMTS). In the frame of the present study we set out to compare the participation of this mechanism in antinociceptive and anti-inflammatory effects of inorganic sodium polysulfide (POLY) and DMTS in carrageenan-evoked hind paw inflammation. Inflammation of murine hind paws was induced by intraplantar injection of carrageenan (3% in 30 µL saline). Animals were treated intraperitoneally with POLY (17 µmol/kg) or DMTS (250 µmol/kg) or their respective vehicles 30 min prior paw challenge and 6 times afterwards every 60 min. Mechanical pain threshold and swelling of the paws were measured by dynamic plantar aesthesiometry and plethysmometry at 2, 4 and 6 h after initiation of inflammation. Myeloperoxidase (MPO) activity in the hind paws were detected 6 h after challenge by luminescent imaging. Mice genetically lacking TRPA1 ion channels, sst4 receptors and their wild-type counterparts were used to examine the participation of these proteins in POLY and DMTS effects. POLY counteracted carrageenan-evoked mechanical hyperalgesia in a TRPA1 and sst4 receptor-dependent manner. POLY did not influence paw swelling and MPO activity. DMTS ameliorated all examined inflammatory parameters. Mitigation of mechanical hyperalgesia and paw swelling by DMTS were mediated through sst4 receptors. These effects were present in TRPA1 knockout animals, too. DMTS inhibited MPO activity with no participation of the sensory neuron-SOM axis. While antinociceptive effects of POLY are transmitted by activation of peptidergic nerves via TRPA1, release of SOM and its effect on sst4 receptors, those of DMTS partially rely on SOM release triggered by other routes. SOM is responsible for the inhibition of paw swelling by DMTS, but TRPA1 does not contribute to its release. Modulation of MPO activity by DMTS is independent of TRPA1 and sst4.